Evaluation of corn and soybean response to phosphorus and potassium fertilization - Arns, Ingrid (Kansas State University, 2013)
Corn (Zea mays) response to fertilization and placement methods has been studied extensively; however studies on soybean [Glycine max (L.) Merr.] response to placement have been limited. Three studies were completed to evaluate different aspects of crop response. The objective of the first study was to evaluate the effect of starter and broadcast fertilizer application on corn and soybean, in a typical corn-soybean rotation in Kansas. Treatments were unfertilized control, starter (N, P and K), broadcast P and K using mono ammonium phosphate (MAP) and potassium chloride (KCl) and the combination of starter and broadcast. Corn and soybean yield generally was not affected by starter and broadcast treatments. Thus fertilization may be recommended only under specific conditions. The objectives of the second study were (i) to evaluate the effect of residual and direct fertilization on soybeans after corn under a corn-soybean rotation system, and (ii) study the effect of fertilizer P and K application on soil test P (STP) and soil test K (STK) changes over time. Direct fertilization increased soybean yield while residual fertilizer did not. Therefore maintenance rates may be effective to improve soybean yield and likely maintain STP and STK levels. Application of P and K fertilizer generated significant increases in STP and STK after one year of application. The rate of P and K fertilizer required to increase 1 mg kg-1 yr-1 was between 2.8 - 5.1 kg ha-1 for P and between 1.0- 2.5 kg ha-1 for K, respectively. The objective of the third study evaluate both corn and soybean response to direct P fertilization including starter and broadcast. The treatments were a control, two starter fertilizers (with N-P and N only), five P rates (9.8, 19.6, 29.3, 39.1, 48.9 kg P ha-1) and one treatment with starter fertilizer in addition to the broadcast fertilizer application. Corn grain yield was not significantly affected by any broadcast or starter treatments. Broadcast application rates significantly increased soybean yield on low STP levels. Results of this study show that large corn or soybean yield response to starter and broadcast P application are likely with low STP levels.
Keywords: Starter; Broadcast; Phosphorus; Placement; Fertilization; Potassium; Agronomy (0285)